Risk Financing Transfers and Risk Retention : A Semantic Literature Analysis for Financial Stability - Deni Sunaryo; Yoga Adiyanto; Iffah Syarifah; Salwa Dita; Diana Salsa Bella (Harmony Management: International Journal of Management Science and Business, 2024)
The increasingly dynamic global financial landscape demands effective risk management strategies to ensure financial stability and institutional sustainability. Two critical approaches, risk financing transfers and risk retention, offer complementary solutions. Risk financing transfers allow institutions to redistribute financial risks to third parties through mechanisms such as securitization and Credit Risk Transfers (CRTs), improving market efficiency. In contrast, risk retention emphasizes accountability by require institutions to retain a portion of the risks, fostering market discipline and investor confidence.This study employs a Semantic Literature Review (SLR) to analyze the interaction between these approaches, focusing on mechanisms like securitization, contract design, and macroprudential policies. By reviewing ten peer reviewed articles published between 2015 and 2024, key themes and challenges related to systemic risks, moral hazards, and regulatory gaps are identified. Thematic analysis, supported by tools like NVivo, reveals the potential of these mechanisms to enhance financial stability when implemented within a robust regulatory framework.The results highlights that while risk financing transfers increase flexibility and market efficiency, they May exacerbate moral hazards without sufficient risk retention. Macroprudential policies and accurate risk pricing is crucial in addressing systemic risks, particularly in sectors like shadow banking and climate vulnerable regions. The study also underscore the importance of transparent contract design and the integration of innovative tools, such as geospatial data and machine learning, to support fair and efficient risk distribution.In conclusion, balancing market efficiency and systemic risk mitigation is imperative.While​ risk retention strengths accountability and oversight, effective integration with risk financing transfers is necessary to create a sustainable and resilient financial system.This​ review provides valuable insights for policy makers and practitioners in addressing emerging financial challenges.